TRIGGERING EMOTIONAL VALUE THROUGH AESTHETICS OF COMPACT CAR DESIGN IN MALAYSIA - Muhamad Aiman Afiq Mohd Noor; Azhari Md Hashim (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The relationship between typicality and novelty was discussed in order to identify the significant emotional value arising in the compact car design of Malaysian manufacturers. Typicality and novelty usually are associated with the aesthetic preference of human artefacts as in this study in compact car design. Considering a typical product is rarely new and, conversely, a novel product often labelled as typical, the positive effects of both features seem incompatible. This paper discusses the history of the Malaysian manufacturer’s compact car design according to its timeline and the current market based on its model and achievement. Furthermore, the relationship between compact car design such as the limitation of emotional value arising through typicality and novelty of specific compact car design and how it triggers the user’s perception through its aesthetics form. Hence, a pilot study was conducted to validate a set of stimulus and questionnaires as a way to formulate an actual survey. Finally, the outcome of this study will suggest a way forward in exploring typicality and novelty through a reliable method of compact car design.